Strategi Peningkatan Kompetensi Pendidik Islam Di Madrasah Ibtidaiyah M Three Dalam Tinjauan Filsafat Ilmu - Putri, Silviana; Nugraha, Mulyawan Safwandy (Peneliti.net, 2025)
This research examines the application of philosophy of science in the training of Islamic educators with a critical approach to improve the quality of education, especially in Madrasah Ibtidaiyah M Three, Bandung Regency. Philosophy of science, which includes aspects of epistemology, ontology and axiology, provides a conceptual framework for educators to understand knowledge more deeply and integrate it with Islamic values. The research used a qualitative approach with a case study method, involving in-depth interviews with teachers and madrasah principals, as well as observation of the training implementation. The results show that the application of philosophy of science in the training of Islamic educators at Madrasah Ibtidaiyah M Three has enriched teachers' understanding of ethical and moral values-based teaching, and improved reflective abilities in the learning process. The training also encouraged innovation in curriculum development and teaching methods that are more relevant to students' needs. In conclusion, the application of a critical approach based on the philosophy of science has the potential to improve the overall quality of Islamic education through improving teachers' pedagogical, professional, personality and social competencies.